Sensitivity of Salmonellae to antibiotics and nitrofurans - Γκιθκόπουλος, Π. Ρ. (Journal of the Hellenic Veterinary Medical Society, 2019)
193 strains of Salmonella gall imam m, 47 strains of S. pullorum and 14 strains of motile salmonellae, isolated during the period 1975-1982 from several species of birds, were tested against the antibiotics: ampicillin, neomycin, streptomycin, kanamycin, terramycin, aureomycin, chloramphenicol and the nitrofurans: furaltadone, furazolidone, by the disc method in Mueller Hinton agar. S. gallinarum was more sensitive to nitrofurans (furazolidone and furaltadone) but the difference was significant (P<0.5) only to aureomycin, neomycin and streptomycin. Apart to nitrofurans, S. pullorum was very sensitive to cloramphenicol. The sensitivity of motile salmonellae to ampicillin was very high